Financing Local Governments: Exploiting the potential of local revenue - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
Over the years, the inadequacy of locally generated revenue has remained a major challenge for Local Governments (LGs). Besides the generally slow growth in revenues, the real value has been declining especially since financial year (FY) 2004/05 when Graduated Tax was suspended. As a result, the contribution of locally generated revenues has declined significantly. This has led to dominance of Central Government (CG) transfers for financing. However, these are largely conditional, thus eroding the fiscal discretionary power of LGs. There is an increasing inability of LGs to finance operation and maintenance of their investments in the wake of reducing local revenues. Therefore, LGs do not have the flexibility to exercise discretion in spending especially on the maintenance of the infrastructure stock. As a result, the focus has been more on minor repairs leading to a backlog of rehabilitation and reconstruction which is partly the cause of breakdown of public infrastructure investments like boreholes, bridges, and roads. In an attempt to compensate this shortfall, Government introduced two new sources of revenue: The Local Government Hotel Tax (LGHT) and the Local Services Tax (LST). The two newly introduced taxes have been unable to fully compensate for Graduated Tax leaving a financing gap. The Budget Monitoring and Accountability Unit field findings indicate that the local revenue collected across most LGs cannot even cover the sitting allowances for councilors in a FY. Financing for LGs therefore remains among the most critical policy issues in LG administration in Uganda. Owing to the development responsibilities placed on LGs, there is need for adequate financing. This policy brief, explores what can be done to improve local revenue collections.